2021
DOI: 10.3390/agronomy11020331
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Jasminum parkeri: A Critically Endangered Wild Ornamental Woody Shrub from Western Himalaya

Abstract: Jasminum parkeri Dunn is a narrowly endemic, critically endangered woody ornamental shrub confined to sub-temperate zone of Western Himalayas, and rediscovered from its type locality after a lapse of about 100 years. In the present study, a propagation technique of J. parkeri, using stem cuttings, was established for the first time through application of auxins, namely, indole-3-acetic acid (IAA), 1-naphthaleneacetic acid (NAA), and indole-3-butyric acid (IBA), at varying concentrations ranging from 1000 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Cutting success, entailing quality AR formation with high rooting percentage, depends on numerous factors, such as cutting type, environmental conditions, nutritional levels of the stock plant, rooting medium and phytohormone application [17,71,72]. IBA has been reported to increase in vivo adventitious root formation, overall quality and uniformity of roots in many ornamental species [73][74][75][76][77][78][79][80][81][82]. Untreated stem cuttings (C0) were also able to root, but with a lower rooting percentage, in comparison to IBA-treated cuttings, possibly due to the presence of stored carbohydrates and endogenous auxin contents in the cuttings [83].…”
Section: Discussionmentioning
confidence: 99%
“…Cutting success, entailing quality AR formation with high rooting percentage, depends on numerous factors, such as cutting type, environmental conditions, nutritional levels of the stock plant, rooting medium and phytohormone application [17,71,72]. IBA has been reported to increase in vivo adventitious root formation, overall quality and uniformity of roots in many ornamental species [73][74][75][76][77][78][79][80][81][82]. Untreated stem cuttings (C0) were also able to root, but with a lower rooting percentage, in comparison to IBA-treated cuttings, possibly due to the presence of stored carbohydrates and endogenous auxin contents in the cuttings [83].…”
Section: Discussionmentioning
confidence: 99%
“…The application of NAA improved the rapid recovery of the wounded surface and also affected the rapid appearance of adventitious roots, which guaranteed the cuttings' survival rates. It was reported in a study that 0.3% of NAA concentration resulted in the highest rooting percentage of Jasminum parkeri [31]. It was also reported that just 0.01% NAA in combination with 0.01% GA 3 can improve rooting percentage of Hydrangea [45].…”
Section: Discussionmentioning
confidence: 93%
“…Rooting stimulants can be used to increase the rooting capacity of different plants [27][28][29][30][31] and for obtaining the maximum number of rooted cuttings in a short period of time [32]. However, some studies concluded that rooting media is also an important factor which could affect rooting percentage in different ornamental cuttings [1,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, different concentrations of auxins such as indole-3-butyric acid (IBA) and α-naphthaleneacetic acid (NAA) are applicable to plants, and they are highly effective for rooting [8,9]. Growth regulators are effective for rooting in woody plants during cutting propagation [10], and many studies are being conducted on growth regulator treatment for propagating woody plants for South Korean endemic plants [11][12][13]. Further, cutting propagation for Rhododendron shows that IBA and NAA treatments are effective for the reproduction of eight Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%